An Improved Modified Capacitor-Assisted Z-Source Inverter with Reduced Capacitor Voltage Stress and Inrush Start-up Current - Subhani, N. (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper aims to develop a new improved series modified capacitor assisted Z-source inverter (SMCA-ZSI) with reduced capacitor voltage stress and inrush start-up current. The impedance network of the proposed topology maintains the same number of components count and inverter outcome similar to traditional MCA-ZSI. The key advantages of the proposed topology are the reduced voltage stress on the main components of ZSI impedance network, i.e., capacitors. Besides, the inrush start-up current also reduced for the series connection of the whole impedance network from input DC side to output AC side. Moreover, the proposed topology provides a common ground which can help to reduce the leakage current in the photovoltaic application. For the common ground sharing feature, which is not available in the conventional MCA-ZSI, the SMCA-ZSI topology can be categorized as a doubly grounded inverter topology. The improved performances of the proposed SMCA-ZSI have been demonstrated by simulation results which are performed in Matlab/Simulink software. Â© 2019 IEEE.